Lipoproteins in diabetes mellitus - Toth, Peter P.; Lyons, Timothy J.; Jenkins, Alicia J. (Contemporary Diabetes,, 2014)
Diabetes mellitus has become epidemic on a global scale, and millions of new cases are diagnosed every year. The epidemic of diabetes mellitus is expected to result in one of the steepest rises in human morbidity and mortality ever observed outside of wartime. Insulin resistance is a hallmark of pre-diabetes and type 2 diabetes mellitus, and is characterized by impaired insulin-signaling transduction.  Authoritative and comprehensive, Lipoproteins in Diabetes Mellitus details the many changes wrought by insulin resistance and diabetes mellitus on lipid and lipoprotein metabolism. The book begins by summarizing the various techniques to measure lipoproteins and their subclasses. The mechanisms by which insulin resistance and diabetes mellitus increase risk for atherosclerosis, diabetic retinopathy, and diabetic nephropathy are then explored in detail. Finally, the effects of  lifestyle modification and the results of clinical trials using established and investigational drugs are discussed.  An invaluable contribution to the literature, Lipoproteins in Diabetes Mellitus is a comprehensive reference on the clinical and scientific aspects of lipoproteins in diabetes. It will have a long-lasting and significant effect on the medical management of people with diabetes.